The Freedman's Story: an Accusation of Witchcraft in the Social World of Early Imperial Roman Italy (CIL 11.4639 = ILS 3001). (19th July 2018) - Macrae, Duncan E.
Abstract: This article proposes a new reading of a late first-centuryc.e. inscribed dedication from Todi (Umbria) as an accusation of witchcraft, a rhetorical text aimed at propagating a particular story among the local community. Historical and anthropological studies of witchcraft accusations in other societies have emphasised how they can reveal tensions and anxieties that are normally not visible to the observer. By drawing on these studies and close examination of the language and content of the inscription, this article analyses an historical agent's experience of the social structure of early imperial Italy. The accusation is read as a freedman's response to his ambiguous position in a slave society, the ambivalent power of writing in Roman culture and the religious claims of Flavian imperial discourse.